Metastatic papillary thyroid cancer with lateral neck disease: Pattern of spread by level1. Issue 10 (10th September 2012) - Merdad, Mazin; Eskander, Antoine; Kroeker, Teresa; Freeman, Jeremy L.
<x xml:space="preserve">Abstract</x> Background Currently, there is no clear consensus on the extent of this lateral neck dissection required in papillary thyroid cancer (PTC) with lateral neck metastasis. The purpose of this study was to review our experience with metastatic PTC, and identify the pattern of lymphatic spread to the lateral neck. Methods A retrospective medical chart review of PTC patients treated with lateral neck dissection (levels II–Vb) at our institution between January 2004 and 2011. A total of 185 patients underwent 248 selective lateral neck dissections. Results Levels II, III, IV, and Vb were respectively involved in 49.3%, 76.6%, 61.6%, and 29.2% of cases. Conclusion We advocate for a routine excision of levels II, III, IV, and Vb in PTC with metastasize to any lateral neck level. Although we have routinely dissected level IIb, it may be appropriate to omit its dissection, as well as level Va, when there are no clinical, radiologic, or intraoperative evidence of disease involving these sublevels. © 2012 Wiley Periodicals, Inc. Head Neck 35: 1439–1442, 2013